Effect of chemical modification of eggshells power filled low density polyethylene composites - Siti Shuhadah Binti Md Saleh (School of Materials Engineering, Universiti Malaysia Perlis, 2010)
The primary objective of this study is to determine the properties and characterization of eggshells filled LDPE composites on different composition with an aim of developing polymer composites material.